Exploring the impact of education on sustainable resource efficiency: the interplay with CO2 emissions, renewable energy, and agriculture in G20 nations - Zhiying, Zhao; Sidi, Zhanglin (Frontiers in Environmental Science, 2025)
This study investigates how key environmental and socioeconomic factors influence educational development capacity in G20 countries over the period 2000–2022. Specifically, it examines the impacts of carbon emissions (CE), freshwater stress (FWS), agriculture, forestry, and fisheries output (AFF), renewable energy use (RE), financial inclusion (FIN), and government education expenditure (GEE) on primary school enrollment (EDC). Using the Method of Moments Quantile Regression (MMQR), the study captures the heterogeneous effects of these variables across the conditional distribution of EDC, offering a nuanced understanding beyond average outcomes. Robustness checks—including matrix correlation, slope heterogeneity, cross-sectional dependence (CSD), CIPS unit root tests, and Westerlund cointegration analysis—ensure the reliability of results. Empirical findings reveal that CE and FWS are negatively associated with EDC across all quantiles, while RE, FIN, and GEE show significant positive effects, particularly at higher quantiles. AFF has a more limited impact, becoming significant only in better-performing segments. These insights highlight the multidimensional nature of education and underscore the importance of integrated environmental and financial policies to enhance human capital formation. The study offers actionable recommendations aligned with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 13 (Climate Action), and SDG 6 (Clean Water and Sanitation).